Wating Longer Before Claiming, and Activating Youth. No Point? - Bart Cockx; Eva van Belle (Center for Economic Studies and ifo Institute (CESifo), 2016)
In Belgium school-leavers are entitled to unemployment benefits after a waiting period and eligible to intensified counselling and training in the Youth Work Plan (YWP) if a job is not found within three months. The length of the waiting period and eligibility to the YWP are sharply determined by two distinct age thresholds. These are exploited to estimate the impact of these policies on the transition rate to employment and on the quality of work. Both policies increase job finding only slightly and insignificantly. The accepted wage is unaffected, but the number of working days falls and, hence, also earnings.
Keywords: J64; J65; J68; 330; youth unemployment; policy evaluation; regression discontinuity design; survival analysis; quality of employment